2014
DOI: 10.3810/psm.2014.09.2077
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Pain of Knee Osteoarthritis

Abstract: Pain from knee osteoarthritis creates a significant burden for symptomatic patients, who are often forced to change their lifestyle because of their symptoms. Activity modification, therapy, weight loss, nonsteroidal anti-inflammatory drugs, shoe orthotics, bracing, and injections are the nonoperative options available. New technologies are also emerging in the treatment of knee osteoarthritis. Ultimately, these therapeutic modalities should reduce pain and increase the overall functioning of patients. These n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 52 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…The number of patients with painful knee due to OA continues to increase dramatically with the aging of society: the estimated number of patients exceeds 25 million in the United States (1) and 8 million in Japan (2). The main symptom of OA is pain, which is also the leading factor for patients making lifestyle changes and seeking medical intervention (3). The objectives of OA management, according to OA Research Society International, are to reduce pain and inflammation, slow-down cartilage degradation, improve function, and reduce disability (4).…”
Section: Abstract Background: Our Previous Research Provided Evidencmentioning
confidence: 99%
“…The number of patients with painful knee due to OA continues to increase dramatically with the aging of society: the estimated number of patients exceeds 25 million in the United States (1) and 8 million in Japan (2). The main symptom of OA is pain, which is also the leading factor for patients making lifestyle changes and seeking medical intervention (3). The objectives of OA management, according to OA Research Society International, are to reduce pain and inflammation, slow-down cartilage degradation, improve function, and reduce disability (4).…”
Section: Abstract Background: Our Previous Research Provided Evidencmentioning
confidence: 99%
“…The main symptom of OA is pain, which is also the leading factor that makes patients change their lifestyle and seek medical intervention (4). According to the OA Research Society International, the objectives of OA management are to reduce pain and inflammation, slow cartilage degradation, improve function and reduce disability (5).…”
mentioning
confidence: 99%
“…Beaudreuil et al (2009) stated the clinical effectiveness of knee sleeve for knee osteoarthritis. Hrnack & Barber, (2014) suggested that knee brace was one of the effective management methods of the pain of knee osteoarthritis. Some studies investigated the alterations in proprioception in humans wearing knee sleeves.…”
Section: Introductionmentioning
confidence: 99%